2018
DOI: 10.1159/000491624
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Circular RNAs Hsa_Circ_0001874 and Hsa_Circ_0001971 as Novel Biomarkers for the Diagnosis of Oral Squamous Cell Carcinoma

Abstract: Background/Aims: Recent studies have demonstrated that circular RNAs (circRNAs) can serve as potential molecular markers for disease diagnosis. However, little is known about their diagnostic potential for oral squamous cell carcinoma (OSCC). This study aimed to determine the expression of circRNAs in the saliva of OSCC patients to identify novel biomarkers for OSCC screening. Methods: Microarray screening of circRNA was performed to identify differentially expressed circRNAs in saliva from 3 OSCC patients com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
84
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(93 citation statements)
references
References 32 publications
5
84
0
Order By: Relevance
“…It was reported that hsa_circ_0008309 and hsa_circ_001242 was significantly downregulated in OSCC tissues, correlated with pathological differentiation of OSCC, and may act as a potential novel biomarker for the diagnosis and treatment of OSCC . In addition, salivary hsa_circ_0001874 and hsa_circ_0001971 also act as biomarkers for diagnosing OSCC . In our study, hsa_circRNA_100533 was significantly downregulated in tissues of patients with OSCC, which suggested that hsa_circRNA_100533 might be a potential diagnostic marker for OSCC.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…It was reported that hsa_circ_0008309 and hsa_circ_001242 was significantly downregulated in OSCC tissues, correlated with pathological differentiation of OSCC, and may act as a potential novel biomarker for the diagnosis and treatment of OSCC . In addition, salivary hsa_circ_0001874 and hsa_circ_0001971 also act as biomarkers for diagnosing OSCC . In our study, hsa_circRNA_100533 was significantly downregulated in tissues of patients with OSCC, which suggested that hsa_circRNA_100533 might be a potential diagnostic marker for OSCC.…”
Section: Discussionsupporting
confidence: 59%
“…11,22 In addition, salivary hsa_circ_0001874 and hsa_circ_0001971 also act as biomarkers for diagnosing OSCC. 23 In our study, hsa_circRNA_100533 was significantly downregulated in tissues of patients with OSCC, which suggested that hsa_circRNA_100533 might be a potential diagnostic marker for OSCC. Furthermore, we also evaluated the expression and biological functions of hsa_circRNA_100533 in OSCC cell lines.…”
Section: Discussionsupporting
confidence: 52%
“…circRNA_100290, on the other hand, functions as a competing endogenous RNA (ceRNA), which regulates other RNA transcripts by competing for shared microRNAs (miRNAs), to antagonize miR-378a-driven GLUT1 suppression, finally leading to the induction of glycolysis and cell proliferation in OSCC 18 . While significant lower expression of circ_0000140 was found in OSCC patients 19 , the molecular mechanism behind this is still unclear.…”
Section: Introductionmentioning
confidence: 95%
“…Increasing studies have reported that circRNAs have the potential to serve as biomarkers to detect cancer. [18][19][20] We used the ROC curve to assess the diagnostic value of circHUWE1 for CRC. The AUC was 0.732 ( Figure 2D), which showed that circHUWE1 may serve as a potential diagnostic biomarker for CRC.…”
Section: Circhuwe1 Was Up-regulated and Could Be Served As A Diagnostmentioning
confidence: 99%